(untitled) (Zoological Records and Reviews, 2023)
Small mammals – rodents, shrews, and insectivores occupying forest floor, understorey, and canopy niches – are keystone components of forest ecosystems, functioning simultaneously as herbivores, seed dispersers, mycorrhizal inoculants, insectivores, and prey for mesopredators and raptors. Their population dynamics – characterised by multi-annual cycles driven by food availability, predation pressure, and density-dependent regulation – have cascading effects on forest regeneration, arthropod community composition, and predator-prey dynamics across multiple trophic levels. This review synthesises evidence from 188 primary studies (2005-2023) examining the population ecology of small mammals in European forest ecosystems, evaluating population dynamics, habitat associations, interspecific interactions, and responses to forest management and climate variability across boreal, temperate, and Mediterranean forest types. Masting events – synchronised mass seed production by beech and oak – drive 2-4 year population cycles in Apodemus flavicollis and Myodes glareolus, with peak densities reaching 80-140 individuals per hectare following mast years and crashes to < 5 per hectare in subsequent mast failures. Forest management intensity significantly affects small mammal diversity: naturally structured forests with high deadwood volume and canopy heterogeneity support 2.4-fold higher small mammal species richness than intensively managed even-aged plantations. Climate variability – particularly drought effects on mast production and the synchrony of masting across Europe – is emerging as a key driver of range-wide population dynamics. Conservation implications for forest management certification, raptor conservation, and tick-borne disease risk management are discussed.